Functional analysis of Rehmannia glutinosa key LRR-RLKs during interaction of root exudates with Fusarium oxysporum reveals the roles of immune proteins in formation of replant disease - Yang, Chuyun; Xie, Zhuomi; Qian, Sheng; Zhang, Junyi; Yu, Zhijian; Li, Mingjie; Gu, Li; Qin, Shuangshuang; Zhang, Zhongyi (Frontiers in Plant Science, 2022)
Previous studies have indicated that some Rehmannia glutinosa Leucine-rich repeat receptor-like protein kinases (LRR-RLKs) are involved in the formation of replant disease. However, it remains unclear how the interaction of LRR-RLKs with a key factor, the interaction between root exudates and Fusarium oxysporum, results in formation of replant disease. In this study, the influences of root exudates, F. oxysporum and the interaction of these two factors on expression of nine R. glutinosa LRR-RLKs (RgLRRs) were analyzed. The resulting eight RgLRRs of them were highly expressed at the early stage, and rapidly declined at later stages under mixed treatment of root exudates and F. oxysporum. The functions of nine RgLRRs under root exudates, F. oxysporum and mixed treatment of root exudates and F. oxysporum were preliminarily analyzed using transient overexpression and RNAi experiments. The results showed that high expression of RgLRR19, RgLRR21, RgLRR23 and RgLRR29 could decrease the damage to root cells from the mixed treatment of root exudates and F. oxysporum, but the interference of these genes enhanced the damage levels of root cells. Based on this, stable transgenic R. glutinosa seedlings were acquired. Overexpression of RgLRR29 conferred resistance of R. glutinosa seedlings to root exudates, F. oxysporum and mixed treatment. These results indicated that the continuous proliferation of F. oxysporum supported by root exudates altered the expression patterns of RgLRRs in R. glutinosa, then disordered the growth and development of R. glutinosa, finally leading to the formation of replant disease.